University Students’ Writing Ability of National Insight-Based Text Genre in University to Support Sustainable Development Goals (SDGs) - Abidin, Zaenal; Zulfadhli, Muhammad; Farokhah, Laely; William, Nanda; Huda, Mochammad Miftachul; Mutaqin, Ejen Jenal (Universitas Negeri Makassar, 2025)
Writing is one of the important language abilities for students in universities. However, previous studies indicate that students' writing ability remains low, primarily due to their inadequate basic writing skills. This research is aimed to describe the students’ writing ability of national insight-based text genre in university. A qualitative approach with descriptive method was used in this research. The research subjects consisted of 30 students in a university located in Bekasi, Indonesia. The research data collection techniques consisted of writing tests of national insight-based text genres and interviews. Research data were analyzed through the data reduction, presentation, and verification. The results showed that generally the average of students’ writing ability of national insight-based text genres was still under the minimum standard of passing grade in writing standard of Indonesian language learning in universities. In descriptive and exposition texts, the most difficulties were found in the aspects of content organization, grammar, style (choice of structure and vocabulary), and spelling and grammar. In the procedure text, the difficulties were found in the five indicators of writing ability. Moreover, the content of national insight on the three types of texts have not been fully internalized in the text. This research provides an opportunity for further research regarding the development of national insight-based of Indonesian language teaching materials for students in universities. This study adds new information regarding sustainable development goals (SDGs).